Properties of sustainable concrete containing recycled fine aggregate as partial sand replacement - Hanis Nadiah, Ruslan; Tanash, Alaa Omar; Khairunisa, Muthusamy; Low, Wee Yang; Mohamed, A.Ismail (Trans Tech Publications Ltd, 2023)
River sand, one of the ingredients for concrete when harvested uncontrollably from the river would cause destruction to the river environment. At the same time, the increasing concrete waste disposed at dumpsite after generated from construction and demolition activity causes environmental pollution. The approach of recycling concrete waste for use as a mixing component in concrete production would lessen the heavy reliance on natural sand supplies and lower the amount of concrete waste disposed. The current study investigates the effect of recycled fine aggregate obtained from concrete waste as sand replacement on concrete's workability, compressive strength, and water absorption. Five mixtures were made using varying amounts of recycled fine aggregate (0, 10, 20, 30 and 40% by weight of sand). All specimens were subjected to water curing. Three types test were conducted namely slump test, compressive strength test and water absorption test. Findings show that the integration of recycled fine aggregate up to 20% produces concrete with the targeted strength of 40MPa. Furthermore, the water absorption of the mixes is less than 3%, allowing it to be classified as good quality. Success in blending recycled fine aggregate in concrete production would contribute to saving river sand consumption and lesser concrete waste for a cleaner environment.